Management of cleft lip and palate in Egypt: A National survey - Abulezz, Tarek Abdelhameed; Elsherbiny, Ahmed K.; Mazeed, Ahmed S. (Indian Journal of Plastic Surgery, 2018)
Background: Variable protocols for the management of cleft lip and/or palate (CLP) patients are currently used. However, to our knowledge, there are no previously published data about cleft management and practice in Egypt. Materials and Methods: One-hundred questionnaires were distributed to cleft surgeons attending the annual meeting of the Egyptian Society of Plastic and Reconstructive Surgeons in March 2016 to investigate timing, techniques and complications of cleft surgery. Seventy-two colleagues returned the questionnaire, and the data were analysed using Microsoft Excel software. Results: The majority of cleft lip cases are repaired between 3 and 6 months. Millard and Tennison repairs for unilateral cleft lip, while Millard and Manchester techniques for bilateral cleft lip are the most commonly performed. Cleft palate is usually repaired between 9 and 12 months with the two-flap push-back technique being the most commonly used. The average palatal fistula rate is 20%. Pharyngeal flap is the method of choice to correct velopharyngeal incompetence. Polyglactin 910 is the most commonly used suture material in cleft surgery in the country. Multidisciplinary cleft management is reported only by 16.5% of participants. Conclusion: Management of CLP in Egypt is mainly dependent on personal preference, not on constitutional protocols. There is a lack of multidisciplinary approach and patients’ registration systems in the majority of centres. The establishment of cleft teams from the concerned medical specialties is highly recommended for a more efficient care of cleft patients.
Keywords: Cleft lip and palate; cleft management; cleft survey; Egypt; multidisciplinary cleft clinic